Protein Cytokines, Cytokine Gene Polymorphisms, and Potential Acute Coronary Syndrome Symptoms. Issue 5 (October 2019) - Mirzaei, Sahereh; Burke, Larisa; Rosenfeld, Anne G.; Dunn, Susan; Dungan, Jennifer R.; Maki, Katherine; DeVon, Holli A.
The purpose of this study was to determine whether relationships exist among protein cytokines, cytokine gene polymorphisms, and symptoms of potential acute coronary syndrome (ACS). Participants included 438 patients presenting to the emergency department (ED) whose symptoms triggered a cardiac evaluation (206 ruled in and 232 ruled out for ACS). Presence or absence of 13 symptoms was recorded upon arrival. Levels of tumor necrosis factor α (TNF-α), interleukin (IL)-6, and IL-18 were measured for all patients. A pilot analysis of 85 patients (ACS = 49; non-ACS = 36) genotyped eight single-nucleotide polymorphisms (SNPs; four TNF and four IL6 SNPs). Logistic regression models were tested to determine whether cytokines or SNPs predicted symptoms. Increased levels of TNF-α and IL-6 were associated with a decreased likelihood of chest discomfort for all patients. Increased levels of IL-6 were associated with a lower likelihood of chest discomfort and chest pressure for ACS patients, and an increased likelihood of shoulder and upper back pain for non-ACS patients. Elevated IL-18 was associated with an increased likelihood of sweating in patients with ACS. Of the four TNF SNPs, three were associated with shortness of breath, lightheadedness, unusual fatigue, and arm pain. In all, protein cytokines and TNF polymorphisms were associated with 11 of 13 symptoms assessed. Future studies are needed to determine the predictive ability of cytokines and related SNPs for a diagnosis of ACS or to determine whether biomarkers can identify patients with specific symptom clusters.